Seminal vesicle metastasis after liver transplantation for hepatocellular carcinoma: A case report. Issue 3 (January 2019) - Shen, Yonghua; Nie, Ling; Yao, Yuling; Yuan, LiQing; Liu, Zhenqing; Lv, Ying
Abstract: Rationale: Cancer recurrence and metastasis after liver transplantation (LT) is common in some hepatocellular carcinoma (HCC) patients. The most common sites of extrahepatic metastases are lung, regional lymph node, adrenal gland, and bone. To our knowledge, HCC metastasis to the seminal vesicle after LT has not been reported in the literature. Patient concerns: A 56-year-old Asian man presented at hospital with a 9-year history of orthotopic LT because of HCC. The patient underwent surgery and radiotherapy for HCC metastasis to adrenal gland and 1 year later, chemotherapy for peritoneal metastasis. A few months later, the patient presented with computed tomography (CT) image showing masses in right lobe of liver, seminal vesicle, and space occupying mass between the spleen and stomach. Diagnoses: Combination of clinical and pathological features revealed the seminal vesicle mass as metastasis from HCC. Interventions: Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) for liver and seminal vesicle lesions was performed and the postoperative pathology revealed malignancy. Thus, the patient underwent surgery and the diagnosis of seminal vesicle metastasis of HCC was confirmed by pathology and immunohistochemical analysis. Outcomes: The patient died due to systemic failure. Lessons: Seminal vesicle metastasis from HCC after LT is rare and there is no consensus on its treatment. Further research into the pathogenesis and therapy of seminal vesicle from HCC after LT is needed to improve outcomes in the rare disease.